Technical Land-Sea Spaces: Impacts of the Port Clusterization Phenomenon on Coasts, Cities and Architectures - Moretti, Beatrice (Journal of Contemporary Urban Affairs, 2023)
Land-sea interactions, extending inland and towards the marine spaces, are affected by major management and design transformations. Globalization processes, port expansion projects and extensive energy transition requests have recently led port institutions to demand more land, engaging deeply with logistics platforms and radically restructuring forms of port governance. In this competitive context, the phenomenon of Port Clusterisation, i.e. the administrative aggregation whereby two or more ports are merged to form port clusters, is heavily impacting the institutional sphere. However, not only does this phenomenon have no control over cities, but its spatial component seems to be neglected by the disciplines of space, such as urbanism and architecture. As a result, port and city institutions lack design tools to tackle urgent challenges as coastal utilization, the need for resilient port-city infrastructures and the regeneration of the port-city architectural heritage.  In terms of novelty and contribution to academia, an examination of the spatial footprint of port clusters will allow research to move beyond its state-of-the-art by targeting a phenomenon that, though pivotal, is under-researched, especially within the spatial disciplines.